'Struggling to be the alpha': sources of tension and intimate partner violence in same-sex relationships between men. Issue 8 (2nd August 2016) - Goldenberg, Tamar; Stephenson, Rob; Freeland, Ryan; Finneran, Catherine; Hadley, Craig
Abstract: In countries such as the USA, gay and bisexual men experience high rates of intimate partner violence. However, little is known about the factors that contribute to this form of violence. In this study, we examine gay and bisexual men's perceptions of sources of tension in same-sex male relationships and how these may contribute to intimate partner violence. We conducted seven focus-group discussions with 64 gay and bisexual men in Atlanta, GA. Focus groups examined men's reactions to the short-form revised Conflicts Tactics Scale to determine if each item was considered to be intimate partner violence if it were to occur among gay and bisexual men. Analysts completed a thematic analysis, using elements of grounded theory. The sources of tension that men identified included: gender role conflict, dyadic inequalities (e.g. differences in income, age, education), differences in 'outness' about sexual identity, substance use, jealousy and external homophobic violence. Results suggest that intimate partner violence interventions for gay and bisexual men should address behavioural factors, while also focusing on structural interventions. Interventions that aim to reduce homophobic stigma and redefine male gender roles may help to address some of the tension that contributes to intimate partner violence in same-sex male relationships.